(untitled) (International Journal of Engineering and Computer Science, 2017)
Presently in the system patient need to contact a doctor and take an appointment is possible only if patient goes to that particular doctor’s clinic. Even the people can’t get the correct information about doctors, their details and different hospitals available in a particular city. The only way to get all these are through directly contacting particular persons personally and it’s a very big problem for a person new to that city. Those who want to have some information in the medical field or wants to get appointment to particular doctor from his own place are not possible. Nowadays in order to get correct information and right treatment for a patient has to go by him wherever needed. This is a lengthy process, which takes a lot of time to design manually, and also costs more and even limited to certain extent. It’s not possible to get all the information or details as well as we can’t satisfy the user through this process. So, this “E-Clinic” website will provide all the information regarding different types of therapy available in clinic and patient can easily book the appointment.